Nonprofits and Change: Building Competencies for the Future - Hunt, Kathryn; Clark, Ernest; Johnson, Anne (Maine Policy Review, 1997)
Nonprofit organizations are connected integrally to the communities in which they exist. They are important providers of health care and social services, libraries and the arts, and education for children and adults. They form the local associations we join as volunteers. Today, many of these same nonprofits face the need to change in order to survive into the 21st century. This article describes the imperative to change currently faced by nonprofit organizations and presents eight core competencies for surviving the future. It is intended for nonprofit leaders, practitioners, and board members alike.